Considerations for new manganese analytical techniques for drinking water quality management. Issue 3 (6th June 2022) - Pei, Yu; Prepas‐Strobeck, Natasha S.; Payne, Sarah Jane; She, Zhe
Abstract: Manganese (Mn) is a contaminant of emerging concern in drinking water, as recent epidemiologic evidence suggests an association between Mn exposure in drinking water and negative neurodevelopmental effects. The nature of Mn events in distribution systems can be sporadic and difficult to predict, with conventional laboratory methods being limited in their ability to provide the flexible on‐line Mn monitoring. Emerging methods such as colorimetric and electrochemical methods offer advantages for monitoring as they have potential to be less expensive, rapid, and readily deployed in the field. These emerging methods, however, face hurdles to adaptation and acceptance including demonstration of sufficient accuracy, precision, sensitivity and yet‐to‐be resolved issues with interfering agents. These hurdles are not insurmountable, and investment is warranted in these novel methods to address pressing needs by the water industry to protect human health. This review paper highlights the opportunities and advantages of advancing field‐testing techniques for Mn management.